2016
DOI: 10.3389/fpls.2016.00975
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Mediated Transcriptome Profiling Reveals Activation of Multiple Regulatory Pathways in Arabidopsis thaliana

Abstract: Imbalance between the accumulation and removal of nitric oxide and its derivatives is a challenge faced by all plants at the cellular level, and is especially important under stress conditions. Exposure of plants to various biotic and abiotic stresses causes rapid changes in cellular redox tone potentiated by the rise in reactive nitrogen species that serve as signaling molecules in mediating defensive responses. To understand mechanisms mediated by these signaling molecules, we performed a large-scale analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 144 publications
(153 reference statements)
6
99
0
Order By: Relevance
“…Like ROS, NO is highly reactive and capable of post‐translationally modifying proteins at cysteine residues, via S‐nitrosylation. This modification can regulate the stability, subcellular localization, and activity of the target proteins (Tada et al ; Lindermayr et al ; Gibbs et al ), causing global changes in gene expression (Hussain et al ). Using shotgun proteomics, a number of S‐nitrosylated proteins have been identified (Puyaubert et al ; Hu et al ).…”
Section: Heat Shock Signaling Mechanismsmentioning
confidence: 99%
“…Like ROS, NO is highly reactive and capable of post‐translationally modifying proteins at cysteine residues, via S‐nitrosylation. This modification can regulate the stability, subcellular localization, and activity of the target proteins (Tada et al ; Lindermayr et al ; Gibbs et al ), causing global changes in gene expression (Hussain et al ). Using shotgun proteomics, a number of S‐nitrosylated proteins have been identified (Puyaubert et al ; Hu et al ).…”
Section: Heat Shock Signaling Mechanismsmentioning
confidence: 99%
“…It has been reported that NO positively regulates PRMT5 activity by S-nitrosylation at Cys-125 under NaCl stress in A. thaliana [20]. Treatment with NO donor S-nitrosocysteine also prominently promotes JMJs expression in A. thaliana [87], implying that JMJs are possibly regulated by NO.…”
Section: Redox Adjustment Of Histone Methylationmentioning
confidence: 93%
“…In addition to influencing SAM synthesis, redox intermediates also regulate the expression and activity of HMTs and HDMs. For instance, application of S-nitrosocysteine, a NO donor, to Arabidopsis leaves upregulates the expression of Set Domain Group 20, a gene encoding lysine methyl transferase, and PcG Histone Methyltransferase Curly Leaf gene [87], pointing to the important function of NO in modulating the two HMTs. PRMT5 can catalyzes Arg symmetric dimethylation of histones and non-histone proteins in higher eukaryotes [88].…”
Section: Redox Adjustment Of Histone Methylationmentioning
confidence: 99%
“…All the A. thaliana HMA ( AtHMA ) domain-containing genes that showed differential expression toward CysNO-mediated transcriptome analysis (Hussain et al, 2016) were identified and heat map showing the signal intensities of differentially expressed genes (up and down-regulated) was generated using R (version 3.3.1). Sequences for all AtHMA genes were retrieved from the Arabidopsis Information Resource (TAIR) database 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we adopted a combined in silico and biological approach to examine structure and putative function of the Arabidopsis thaliana HMA domain containing gene ( AT1G51090-AtHMAD1 ) that showed differential expression in response to CysNO in a separate study involving transcriptomic analysis (Hussain et al, 2016). We also sought to determine its possible role in the regulation of oxidative and nitrosative stress and plant defense against virulent and avirulent pathogens.…”
Section: Introductionmentioning
confidence: 99%